Postmodernism in The Art Concept of Putu Wijaya - Aslan Abidin; Nurhayati Rahman; Inriati Lewa (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This research will explore the life journey of a prominent Indonesian writer, Putu Wijaya. His life history is traced especially his connetion to  traditionality and modernity, starting from childhood until graduating from high school in Bali, as a student to his graduation in Yogyakarta, then moving to settle and making art in Jakarta. The three places gave him an intense understanding of the traditionalities of Bali, Java, and the Archipelago. At the same time, the three places also provide him with an understanding of modernity. The various forms of traditionality and modernity mingled in Wijaya’s works, traditionalities such as fairy tales, wayang stories, and even mystical things that do not make sense also influence Wijaya's way of thinking. Meanwhile, one of the important modernities that also influenced him since childhood was Indonesian language. The language was chosen and designed based on the modern thinking of linguists Von de Wall, HC Klinkert, and Van Ophuijsen from the Dutch colonial state. Wijaya's mingling of traditionality and modernity allows him to write fluently various things, including the absurd and the absurd. His understanding of himself and his readers who were victims of feudalism and colonialism, made him write literary works to make his readers think more freely. This makes Wijaya's literary works tend to have a postmodernist style